Mesopore-dominated hollow carbon nanoparticles prepared by simple air oxidation of carbon black for high mass loading supercapacitors. (30th April 2020) - Fan, Chengwei; Dong, Yue; Liu, Yifan; Zhang, Lihui; Wang, Dengke; Lin, Xieji; Lv, Yan; Zhang, Su; Song, Huaihe; Jia, Dianzeng
Abstract: With the ever-increasing demands for miniaturization of high-power supercapacitors, carbon materials maintaining good rate capability at high mass loadings are urgently needed. Herein, we prepare mesopore-dominated hollow carbon nanoparticles with good capacitive performance from commercial carbon black through an extremely simple air oxidation method. Taking advantage of the crystallinity inhomogeneity of carbon black nanoparticles, the hollow carbon nanoparticles are prepared by selective removal of the amorphous cores while maintaining of the ordered skins. The hollow carbon nanoparticles show large inner cavities, perforated mesoporous structure, and increased surface area from 87.4 to 753.2 m 2  g −1, providing abundant electrolyte reservoirs, ion migration channels, and active sites especially for thick electrodes. The sample shows a dramatically enhanced capacitance from 5 F g −1 of the carbon black to 175 F g −1 . Importantly, the assembled symmetric device exhibits high areal capacitance of 2.31 F cm −2 at 1 A g −1 and remarkable rate performance of 1.59 F cm −2 at 10 A g −1 even with an ultrahigh mass loading of 15 mg cm −2 . Our work helps the deep understanding of the structural transformation of carbon black, and provides a scalable preparation route for hollow carbon nanoparticles with great potential for supercapacitors application. Graphical abstract: Mesopore-dominated hollow carbon nanoparticles prepared by air oxidation of carbon black nanoparticles show high capacitive and fast electrochemical kinetics at high mass loadings due to abundant electrolyte reservoirs, perforated porous structure, and high surface area. Image 1 Highlights: Hollow carbon nanoparticles were prepared by air oxidation of carbon black. Interconnected perforated porous structure enable fast ion transport kinetics. The sample shows remarkable rate performance especially at high mass loadings.